New Site-Specific Dance: a New Style of Intelligent Bodies - Hauna, Miftakhul; Pamardi, Silvester (Journal of Social Research, 2023)
The development of works of art born by extraordinary people is increasingly here, giving birth to new styles born from the corner of space outside conventional stage spaces. This phenomenon began to arise starting with the ideas of art criticism of conventional stages, after which several works were born that began to be performed outside conventional stages. Dance is one of the objects explored in artists' creative spaces, including academic spaces, so that the process of the creative space is born dance works with a new identity based on the development of science and technology. Dance that was born in the context of a special space is called Site Specific Dance, which is a dance work born from the journey of the process to a special location. Where this process targets the dancer's knowledge of space, time, and audience. Architecture, atmosphere, or others from one region that if inspired by the creator of the work, then will be explored how the intelligences of the body are in a special scope that has been chosen. This research uses the 3R method by Eko Supriyanto, Re-Invitating, Re-Questioning, Re-Interpretating, then the results of the research will be processed using the Site Specific Dance method, after which it is presented in a place that has been engineered with special decorations and contradictions to the previous area or location which is used as a process with the Site Specific Dance method. The target of this study is a kind of new presentation style of the Site Specific Dance process.